Agrochem enterprise: husk pesticides / Muhammad Hazmi Zailani [et al.] - Zailani, Muhammad Hazmi; Roslan, Muhammad Khairul Shahril; Ab Aziz, Farah Liyana; Jais, Nur Adilah; Ahamad Kamal, Nurul Ashikin (2016)
Agrochem Enterprise is a business that basically provide an innovation of pesticides. These product were initially designed for better environment.